Karacak Valley Tourism Development Strategy, Garut District, West Java - Adhya, Ilham; Anggayuda Pratama , Bayu; Hendrayana, Yayan (Asosiasi Ahli Administrasi Indonesia, 2024)
Garut Regency has great potential for tourism development thanks to its wealth of natural resources. However, many tourist destinations in this region are unsustainable due to a lack of adequate understanding and capacity in their management. Wana Wisata Karacak Valley, is one of the destinations managed by BKPH Cibatu KPH Garut Perum Perhutani Divre West Java and Banten. Even though it has attractive natural beauty, the number of visitors to Karacak Valley has decreased drastically during the COVID-19 pandemic. Observations show that Karacak Valley has attractions in the form of natural beauty, dense vegetation and waterfalls, but there has been no in-depth study of its development strategy. This research aims to develop a management strategy for the Karacak Valley Tourism Area using a SWOT analysis approach. The results of the study show that the potential of the Karacak Valley includes the beauty of pine vegetation, diversity of animals, accessibility supported by local transportation, and adequate accommodation. The proposed development strategy includes collaboration with regional and village governments, increasing promotion through educational tourism programs and social media, as well as improving security facilities in the waterfall tourist area. With this strategy, it is hoped that the Karacak Valley can be developed optimally and sustainably, providing economic benefits for local communities, as well as preserving its natural environment. Good management will ensure that Karacak Valley remains an attractive and competitive tourist destination in the future.